Optimization of Cyanidation Parameters in the Merrill-Crowe Method for Copper Recovery from Electroplating Wastewater - Afrianti, Lia; Haryati, Tanti; Mintadi, Mukh; Asnawati, Asnawati; Oktavianawati, Ika; Andarini, Novita; Sulistiyo, Yudi Aris; Suwardiyanto, Suwardiyanto (Department of Chemistry, FMIPA, UNEJ, 2026)
Electroplating wastewater contains heavy metals (copper, chromium, zinc, and nickel) at concentrations that frequently exceed safe discharge limits, posing serious risks to aquatic ecosystems. This study examines whether the Merrill–Crowe process, conventionally used for gold and silver recovery, can be adapted to recover copper from industrial electroplating effluent. The wastewater tested carried an initial copper concentration of 235.7 ppm. Cyanidation conditions were optimized by varying pH (7-11) and contact time (5-25 hours) to generate copper–cyanide complexes, which were subsequently precipitated with zinc powder. Complex formation was monitored by UV-Vis spectrophotometry; copper concentrations were quantified by atomic absorption spectrophotometry. Optimal conditions were pH 8 and 20 hours of contact time. Under these parameters, copper recovery reached 58.5% from electroplating wastewater and 43.5% from a standard reference solution. The higher efficiency in the wastewater sample reflects the presence of pre-formed copper–cyanide complexes, which accelerated both cyanidation and cementation. These results suggest the Merrill–Crowe process is a viable, low-complexity recovery strategy, one that not only reduces copper discharge but returns it in elemental form with potential economic value.